Lenalidomide‐induced eosinophilic pneumonia. Issue 4 (25th April 2017) - Toma, Andrew; Rapoport, Aaron P.; Burke, Allen; Sachdeva, Ashutosh
Abstract : Multiple myeloma is a plasma cell dyscrasia accounting for 10% of haematologic malignancies. Lenalidomide is an immunomodulatory drug analogous to thalidomide that is approved for use in patients with myelodysplastic syndrome, and in combination with dexamethasone for refractory or relapsed multiple myeloma. Lenalidomide is preferred to thalidomide because of reduced toxicity, and pulmonary side effects are considered rare. We present, to our knowledge, an unusual and first reported case of a patient with relapsed multiple myeloma who received lenalidomide after autologous stem cell transplant, then developed eosinophilic pneumonia presenting as dyspnoea, peripheral eosinophilia, and bilateral pulmonary opacities. Bronchoscopy with bronchoalveolar lavage was negative for infection, and transbronchial lung biopsies showed eosinophilic pneumonia. After discontinuation of lenalidomide and initiation of prednisone therapy, his dyspnoea improved and eosinophilia resolved; however, symptoms recurred when the drug was restarted at a lower dose, confirming its causative role. In the absence of infection, clinicians should always bear in mind drug toxicity in the differential diagnosis of patients receiving lenalidomide and related agents. Abstract : Lenalidomide‐induced pulmonary toxicity is previously reported; however, eosinophilic pneumonia as a distinct pathological entity is a unique presentation and we report such a case along with a review of the literature.